O SENTIDO DO MISTÉRIO NA TEOLOGIA SISTEMÁTICA DE PAUL TILLICH - Silva, Sandro Graciliano Souza (2012)
This research intends to demonstrate the mystery on Paul Tillich s Systematic Theology. It certifies that the mystery is the manifestation of the sacred for the human being knowledge. Nevertheless, this research concludes that the human being unites to the divine from the knowledge of the revelation of the mystery. Tillich says that the existential knowledge is based on an encounter in which a new meaning is created and recognized. The revelation of the mystery is an existential knowledge and its manifestation in the human bearer of revelation comes to know another person, he knows his history and participates in the reality in which the mystery is revealed in its totality. The mystery is the manifestation of the sacred, for that its revelation causes profound changes in the human being. In Tillich s Systematic Theology the mystery is described as a mark of revelation, its first mark. However as we approach to the text we see that the mystery is more than a mark to Tillich, the mystery is the manifestation of the ground of being, the mystery is the manifestation of the divine that communicates symbolically to the human being from the final revelation of Jesus as the Christ.